Household wealth and the measurement of economic well-being in the United States - Edward N. Wolff; Ajit Zacharias (Levy Economics Institute of Bard College, 2006)
The standard official measure of household economic well-being in the United States is gross money income. The general consensus is that such measures are limited because they ignore other crucial determinants of well-being. We modify the standard measure to account for one such determinant: household wealth. We then analyze the level and distribution of economic well-being in the United States during the 1980s and 1990s, using the standard measure and a measure that differs from the standard in that income from wealth is calculated as the sum of lifetime annuity from nonhome wealth and imputed rental-equivalent for owner-occupied homes. Our findings indicate that the level and distribution of economic well-being is substantially altered when money income is adjusted for wealth. Over the 1989-2000 period, median wellbeing appears to increase faster when these adjustments are made than when standard money income is used. This adjustment also widens the income gap between African Americans and whites, but increases the relative well-being of the elderly. Adding imputed rent and annuities from household wealth to household income considerably increases measured inequality and the share of income from wealth in inequality. However, both measures show about the same rise in inequality over the period. Our results contradict the assertion that the working rich have replaced the rentiers at the top of the economic ladder.
Keywords: D31; D6; H4; P16; 330; living standards; household wealth; inequality